Coping Mechanisms for Psychosomatic Symptoms among Aging Roman Catholic German priests - Man-Ging, Carlos I. (Journal of religion and health, 2018)
To identify and investigate coping mechanisms and other factors which may impact upon the psychosomatic symptoms of aging German Roman Catholic priests. A cross-sectional study was conducted among 499 aging German Roman Catholic priests with standardized questionnaires: Brief Symptom Inventory, Coping Inventory Stressful Situations, and Religious Coping Scale. Task-Oriented Coping exhibited a significant difference between the two groups. Multiple regression analyses indicated that psychosomatic symptoms could be best predicted by means of Task-Oriented Coping mechanisms, identification with priesthood, and by a low Negative Religious Coping. The success of adaptive coping processes for older clergy may depend on how they employ strategies, strengthen their spiritual dimensions, and manage important psychosocial aspects of aging. In our sample, Depression and Somatization are explained best by Emotion-Oriented Coping. It is desirable for aging priests to be aware of protective factors like Role Identification, Task-Oriented Coping, and low Negative Religious Coping, which may be helpful in improving their psychological well-being.